Performance of five serological tests in the diagnosis of visceral and cryptic leishmaniasis: a comparative study - Martina Maritati; Alessandro Trentini; Gregory Michel; Stefania Hanau; Matteo Guarino; Roberto De Giorgio; Christelle Pomares; Pierre Marty; Carlo Contini (Journal of Infection in Developing Countries)
Introduction: Leishmaniasis is a major health problem and its diagnosis still represents a challenge. Since consistent evidence on the comparison of serological methods is lacking, our work aims to compare five serological tests for the diagnosis of visceral and asymptomatic leishmaniasis in southern France, a region where leishmaniasis is endemic.